A methodology for automated analysis of SPICE simulation data. (2015) - Sharma, Manoj; Noor, Arti
The paper presents an automation methodology for SPICE-based circuit simulation analysis. Generally, circuit simulators provide text-based output files which require volcanic and error prone efforts during circuit validation process. The task become more arduous for evaluating circuit performance for variant design parameters involved. A typical meticulous analysis process may contain several thousands of data entries which need to be handled with complete conscientiousness. Furthermore, while examining the circuits with said variant parameters the general GUI-based interface provided with CAD tool proves to be meagre for handling the colossal and monstrous data created. To optimise analysis process authors have proposed a methodology. The authors have integrated different distributed flow assisting the designer to analyse and generate charts making use features in Microsoft Excel. From the adoption of the proposed system the authors have successfully reduced the task involved, in the sense of auto generating the Excel-based data for analytical analysis and inferring process.